Syarat Objektif dan Subjektif Penahanan dalam KUHAP 2025 - Moh. Firda Mb. Husain; Roy Marthen Moonti; Ibrahim Ahmad (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2026)
This study analyzes the objective and subjective requirements for detention based on Law Number 20 of 2025 concerning the Criminal Procedure Code, particularly the cumulative relationship between the requirements and the need for standardization of evidence. The study uses normative legal methods with statutory, conceptual, and comparative approaches. Primary and secondary legal materials were collected through literature studies, then analyzed qualitatively with grammatical, systematic, and teleological interpretations. The results of the study indicate that the objective requirements in the form of a criminal threat of five years or more or certain criminal acts are only the initial legal limits. Detention is only valid if supported by at least two valid pieces of evidence, there is at least one concrete situation as stipulated in Article 100 paragraph (5), and is stated in a warrant or judge's decision containing specific reasons. The 2025 Criminal Procedure Code has shifted the basis for detention from abstract concerns to more concrete behavioral indicators. However, some indicators are still evaluative and have the potential to cause differences in interpretation. Therefore, measurable evidentiary parameters, a risk assessment matrix, consideration of non-detention alternatives, documentation of reasons, tiered supervision, and substantive testing through pretrial motions are required. Detention should be considered a measure of last resort that is proportionate, transparent, and testable, and ensures a balance between effective law enforcement and human rights protection. These findings affirm due process of law and respect for the presumption of innocence.